2017
DOI: 10.19082/4202
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress, dissociative and somatization symptoms in spouses of veterans with PTSD in Zahedan, Iran

Abstract: IntroductionSecondary traumatic stress is a disorder which occurs in spouses and people with close relation to someone with posttraumatic stress disorder. Like PTSD, it seems that STS also occurs with other psychiatric problems like somatization and dissociation. This study aimed to determine the relationship between STS and somatization and dissociation symptoms.MethodsThis cross-sectional study was done in 2015 and lasted for one year. Self-report questionnaires assessing secondary traumatic stress symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Researchers found associations between survivors' trauma, poor health and somatization, specified in local pain, or unspecified it terms of unexplained medical symptoms (Lahav, Rodin, & Solomon, 2015;Lahav, Stein, & Solomon, 2016). STS symptoms were associated with somatization symptoms among spouses of veterans whom suffered from PTSD in Iran (Kianpoor, Rahmanian, Mojahed, & Amouchie, 2017). Wives of veterans with combat stress reaction suffered from psychiatric and somatic symptoms, six years after their husbands returned from the war (Mikulincer et al, 1995), while wives of former war prisoners reported higher PTSD-symptoms and negative perceived health (Lahav et al, 2016).…”
Section: Trauma-work and Healthmentioning
confidence: 99%
“…Researchers found associations between survivors' trauma, poor health and somatization, specified in local pain, or unspecified it terms of unexplained medical symptoms (Lahav, Rodin, & Solomon, 2015;Lahav, Stein, & Solomon, 2016). STS symptoms were associated with somatization symptoms among spouses of veterans whom suffered from PTSD in Iran (Kianpoor, Rahmanian, Mojahed, & Amouchie, 2017). Wives of veterans with combat stress reaction suffered from psychiatric and somatic symptoms, six years after their husbands returned from the war (Mikulincer et al, 1995), while wives of former war prisoners reported higher PTSD-symptoms and negative perceived health (Lahav et al, 2016).…”
Section: Trauma-work and Healthmentioning
confidence: 99%
“…The experiences of forensic social workers in dealing with traumatic incidents in their field of work were investigated in this study. The researchers examined the prevalence of STS symptoms, which are classified as intrusion, avoidance and arousal (Kianpoor et al, 2017). The findings revealed that on average intrusion and avoidance symptoms, such as reliving unpleasant memories and feeling emotionally numb, were not frequently reported by respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a connection exacerbates the difficulty of addressing the emotional repercussions of the work, potentially making forensic social workers significantly more susceptible to STS. Research has demonstrated that the symptoms of STS are nearly comparable to those of posttraumatic stress (PTS) symptoms, such as repeating the traumatic incident, avoidance or hyperarousal, although the severity of the symptoms tends to be lower (Kianpoor, Rahmanian, Mojahed and Amouchie, 2017;Oginska-Bulik, Gurowiec, Michalska & Kedra, 2021). Those suffering from STS will exhibit at least some of the symptoms associated with post-traumatic stress disorder (PTSD).…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…When the war ends and the participants return home, many of the physical and psychological effects of experiencing traumatic and life-threatening events on the battlefield reveal themselves to the individual and his relatives. Post-traumatic stress disorder (PTSD) is one of the major problems of experiencing war, which based on the latest statistics, affects approximately 4%-17% of all war veterans ( 1 , 2 ) .The prevalence of such disorder among the survivors of the Iran-Iraq war is higher than the global average prevalence and is estimated to be about 27.8% ( 3 , 4 ). In traditional societies, veterans' wives are expected to care for their PTSD husbands, and without a sense of consent such comprehensive care leads to a compassion-driven fatigue ( 5 ).…”
Section: Introductionmentioning
confidence: 99%